A theoretical study of the Duff reaction : insights into its selectivity - Grimblat, Nicolás (2016)
Fil: Fil: Grimblat, Nicolás. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Química Rosario (IQUIR-CONICET); Argentina.